Relationship between Serum Albumin Level and Monocyte-to-High-Density Lipoprotein Cholesterol Ratio with Saphenous Vein Graft Disease in Coronary Bypass - Akboga, Mehmet Kadri; Yayla, Cagri; Balci, Kevser Gulcihan; Ozeke, Ozcan; Maden, Orhan; Kisacik, Halil; Temizhan, Ahmet; Aydogdu, Sinan (The Thoracic and Cardiovascular Surgeon, 2017)
Background Previous studies proposed that inflammation, oxidative stress, and impaired endothelial dysfunction have a crucial role in occurrence of saphenous vein graft (SVG) disease (SVGD). The aim of this study was to assess the relationship between monocyte-to-high-density lipoprotein cholesterol (HDL-C) ratio (MHR) and serum albumin (SA) level as readily available inflammatory and oxidative stress markers with the presence of SVGD in patients with a coronary bypass.Methods In this retrospective cross-sectional study, a total of 257 patients (n = 112 SVGD [+] [mean age was 65.3 ± 8.4 years, 75.0% males] and n = 145 SVGD [−] [mean age was 66.5 ± 10.1 years, 74.5% males]) were enrolled. At least one SVG with ≥ 50% stenosis was defined as SVGD. Independent predictors of SVGD were determined by logistic regression analysis.Results White blood cell, neutrophil, monocyte, the age of SVG, and MHR were significantly higher, whereas SA level was significantly lower in patients with SVGD. In regression analysis, neutrophil, age of SVG, SA (odds ratio [OR]: 0.232 [0.156–0.370], p < 0.001), and MHR (OR: 1.122 [1.072–1.174], p < 0.001) remained as independent predictors of SVGD. Moreover, age of SVG showed a significant negative correlation with SA (r = − 0.343, p < 0.001) and a positive correlation with MHR (r = 0.238, p < 0.001). In the receiver-operating characteristic curve analysis, the cutoff value of ≤ 3.75 g/dL for SA has a 73.2% sensitivity and 64.8% specificity and the cutoff value of ≥ 12.1 for MHR has a 71.4% sensitivity and 60.0% specificity for prediction of SVGD.Conclusion Consequently, to the best of our knowledge, this is the first study showing a significant and independent association between SA and MHR with SVGD.
Keywords: atherosclerosis; CABG; inflammation; albumin; monocyte/HDL-cholesterol ratio; saphenous vein graft disease